High prevalence of p16 staining in malignant tumors. - Noémi De Wispelaere; Sebastian Dwertmann Rico; Marcus Bauer; Andreas M Luebke; Martina Kluth; Franziska Büscheck; Claudia Hube-Magg; Doris Höflmayer; Natalia Gorbokon; Sören Weidemann; Katharina Möller; Christoph Fraune; et al. (PLoS ONE)
p16 (CDKN2A) is a member of the INK4 class of cell cycle inhibitors, which is often dysregulated in cancer. However, the prevalence of p16 expression in different cancer types is controversial. 15,783 samples from 124 different tumor types and 76 different normal tissue types were analyzed by immunohistochemistry in a tissue microarray format. p16 was detectable in 5,292 (45.0%) of 11,759 interpretable tumors. Except from adenohypophysis in islets of Langerhans, p16 staining was largely absent in normal tissues. In cancer, highest positivity rates were observed in uterine cervix squamous cell carcinomas (94.4%), non-invasive papillary urothelial carcinoma, pTaG2 (100%), Merkel cell carcinoma (97.7%), and small cell carcinomas of various sites of origin (54.5%-100%). All 124 tumor categories showed at least occasional p16 immunostaining. Comparison with clinico-pathological data in 128 vulvar, 149 endometrial, 295 serous ovarian, 396 pancreatic, 1365 colorectal, 284 gastric, and 1245 urinary bladder cancers, 910 breast carcinomas, 620 clear cell renal cell carcinomas, and 414 testicular germ cell tumors revealed only few statistically significant associations. Comparison of human papilloma virus (HPV) status and p16 in 497 squamous cell carcinomas of different organs revealed HPV in 80.4% of p16 positive and in 20.6% of p16 negative cancers (p<0.0001). It is concluded, that a positive and especially strong p16 immunostaining is a feature for malignancy which may be diagnostically useful in lipomatous, urothelial and possibly other tumors. The imperfect association between p16 immunostaining and HPV infection with high variability between different sites of origin challenges the use of p16 immunohistochemistry as a surrogate for HPV positivity, except in tumors of cervix uteri and the penis.